ANÁLISIS FINANCIERO INTEGRAL Y ESTUDIO DE LA RENTABILIDAD ECONÓMICA Y FINANCIERA EN LA CONSTRUCTORA CUEVA MORENO GUSTAVO DE LA CIUDAD DE LOJA PERIODO 2011 - 2012 - Aguilar Cueva, Katterine del Rocio (2018)
The present titled thesis work "INTEGRAL FINANCIAL ANALYSIS AND STUDY OF THE ECONOMIC AND FINANCIAL PROFITABILITY IN THE MANUFACTURER CAVE MORENO GUSTAVO OF THE CITY DE LOJA PERIOD 2011 - 2012", for their exercise you outlines as objectives to Execute the Vertical and Horizontal Financial Analysis with the purpose of knowing the financial structure of the company like the financial position so much to the date of the financial states that is analyzed, verifying the 9 variations suffered in the bills of more importance, to use Indicators that allow to measure the solvency, the activity, the grade of indebtedness and financial leverage, as well as the profitability so much economic as financial of the manufacturer. To present a Report where is evidenced the obtained results of the application of the Integral Financial Analysis and the Grade of the Economic and Financial Profitability, for the execution of the same one was necessary the use of a methodology specifies that it is based on the use of the methods and techniques for the execution of a type analysis that integral all those that allow the obtaining of reliable results for the taking of decisions. By means of the use of the Vertical, Horizontal Analysis, Reason Financial, Analysis of Tendency whose general results are expressed this way: The vertical and horizontal analysis demonstrates a structure and financial position where the assets in the year 2011 were represented in the following way asset current with the 30.11%; active non currents with 69.89%; the passive ones with the USD 4.14, in Passive of short term 11.64% passive non currents and the patrimony with the USD 84.21. For the year 2012 the results were the following 36.19% average assets and 63.81% noncurrent, the passive ones alone the currents were presented with 1.03% and the patrimony with 98.97%. The expressed vertical analysis a significant variation especially in the average asset with a quantity of USD 158.144,2 dollars that means 54.69% this because the bills of banks were increased with 188.4% and the schedules to pay in 64.75% the asset noncurrent grew that is to say in 17.55% it was smaller the growth the vehicle bills and heavy machinery were not increased 10 significantly, the Passive ones had the following behavior they fell in the 91.63 and this is due to that in the year 2012 the bills were canceled of short and I release term. In connection with the Revenues these they presented the following variations an increment for the year 2012 of the USD 189.73 this because in the year 2012 new construction projects were executed. The expenses especially and those but important the operational expenses as the above-mentioned consequence grew in 228.16% In the Analysis of Tendencies he/she settled down that the tendency to increases it is bigger in the bills of Schedules to get paid that although he/she has relationship with the sales these they have a tendency smaller than 34.51% Finally when applying index and or financial reasons are demonstrated that as for liquidity in the year 2011 the company had 7.27 dollars to cover a dollar of their passive ones of short term and in the year 2012 the index grew to the quantity of USD 35.25 dollars that although it means a good liquidity but for this type of companies whose standard is of 2 one can affirm that the company maintains lazy money without producing any profitability as for the work capital it is demonstrated that in the year 2011 had a capital of work of USD 249.388,45 dollars and in the year 2012 USD 434.619,43 what points out a good quantity to pay their passive of short term. The profitability of this company comes from its efficiency in the use of the physical resources (active) sales that it reaches a USD 0.05 of the net margin of utility generated by this sales what reflects extremely low 11 values in the year 2011 to take place and in the year 2012 present 0.04 cent of dollar.